1965
DOI: 10.1021/bi00888a002
|View full text |Cite
|
Sign up to set email alerts
|

Membranous Material of Bovine Milk Fat Globules. I. Comparison of Membranous Fractions Released by Deoxycholate and by Churning*

Abstract: 20,w, of ca. 13 S. Similar lipoproteins were isolated, but in smaller amounts, from untreated buttermilk, a source of membranous material used widely by previous investigators. However, DOC released water-soluble lipoproteins from buttermilk in amounts comparable to those released from intact fat globules. These findings led to the view that the membrane surrounding the milk fat globule consists of two types of lipid-protein complexes, approximately equal in amount, and distinguishable on the basis of their so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

1969
1969
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 16 publications
2
16
0
1
Order By: Relevance
“…They also found that cream washing with salt solutions caused more coalescence of fat globules, and thus, a higher amount of MFGM proteins was obtained with deionised water. Silva et al, 1980;Evans & Pillinger, 1973;Fong et al, 2007;Kanno & Kim, 1990;Le et al, 2009;Mather, 1978;Nielsen & Bjerrum, 1977;Rombaut et al, 2006;Shimizu et al, 1978;Swope & Brunner, 19684 Dowben et al, 1967Erickson et al, 1964;Fink & Kessler, 1985;Hayashi & Smith, 1965;Kanno et al, 1975 Kanno et al, 1975;Kanno & Kim, 1990;Lamothe et al, 2008;Le et al, 2009;Newman & Harrison, 1973;Swope & Brunner, 1968;Yamauchi et al, 1978 Skim milk ultrafiltrate Britten et al, 2008;Fink & Kessler, 1985 Simulated milk ultrafiltrate Le et al, 2009;Morin et al, 2007a 1.5 g KCl L À1 Le et al, 2009;Rombaut et al, 2006 0 Anderson & Cheeseman, 1971;Erickson et al, 1964;Hayashi & Smith, 1965 Phosphate buffer, pH 6.8 Nielsen & Bjerrum, 1977 50 mM phosphate, 0.15 M NaCl, pH 6.8 Le et al, 2009 10 mM TriseHCl, pH 7.5 Mather, 1978 10 mM Tris, 0.14 M NaCl, pH 7.5 Da Silva et al, 1980…”
Section: Effect Of the Variation Of Centrifugal Conditions On The Wasmentioning
confidence: 99%
“…They also found that cream washing with salt solutions caused more coalescence of fat globules, and thus, a higher amount of MFGM proteins was obtained with deionised water. Silva et al, 1980;Evans & Pillinger, 1973;Fong et al, 2007;Kanno & Kim, 1990;Le et al, 2009;Mather, 1978;Nielsen & Bjerrum, 1977;Rombaut et al, 2006;Shimizu et al, 1978;Swope & Brunner, 19684 Dowben et al, 1967Erickson et al, 1964;Fink & Kessler, 1985;Hayashi & Smith, 1965;Kanno et al, 1975 Kanno et al, 1975;Kanno & Kim, 1990;Lamothe et al, 2008;Le et al, 2009;Newman & Harrison, 1973;Swope & Brunner, 1968;Yamauchi et al, 1978 Skim milk ultrafiltrate Britten et al, 2008;Fink & Kessler, 1985 Simulated milk ultrafiltrate Le et al, 2009;Morin et al, 2007a 1.5 g KCl L À1 Le et al, 2009;Rombaut et al, 2006 0 Anderson & Cheeseman, 1971;Erickson et al, 1964;Hayashi & Smith, 1965 Phosphate buffer, pH 6.8 Nielsen & Bjerrum, 1977 50 mM phosphate, 0.15 M NaCl, pH 6.8 Le et al, 2009 10 mM TriseHCl, pH 7.5 Mather, 1978 10 mM Tris, 0.14 M NaCl, pH 7.5 Da Silva et al, 1980…”
Section: Effect Of the Variation Of Centrifugal Conditions On The Wasmentioning
confidence: 99%
“…This is the converse of triglyceride :phospholipid ratios observed in fractions of MFGM prepared by other methods (13,46,67,175). Deoxycholate treatment of washed cream releases about 50 % of the membrane, apparently without disrupting the fat globule (io, 13,67).…”
Section: Triglyceridesmentioning
confidence: 63%
“…Walstra (183) pointed out that the triglyceride content of deoxycholate (DOC) soluble MFGM is less than its phospholipid content (67). This is the converse of triglyceride :phospholipid ratios observed in fractions of MFGM prepared by other methods (13,46,67,175).…”
Section: Triglyceridesmentioning
confidence: 99%
See 2 more Smart Citations